The latest potentials of topical treatment for mycotic skin lesions - Tekwani, Vinisha; Varahabhatla, Vamsi; Reznichenko, Nataliya; Резніченко, Наталія Юріївна (Запорізький державний медичний університет, 2018)
Introduction: Mycotic skin diseases are noninvasive infections which are the most persistent problems in dermatology. In mycotic skin infection, age, relapse inclination, persistent chronic course and resistance to therapy are characteristic. Biphonazole is the new generation antifungal preparation that promisingly has lesser side effects compared to systemic antimycotics. Aim. The aim of our study was to determine the effectiveness and safety of using Biphanazole lotion as topical treatment for patients with mycotic skin lesions. Methods and Materials.The work included 39 patients with various mycoses of different origin. Signs and symptoms of infection were assessed on a scale from mild to severe. Laboratory examination of mycotic infection was performed by direct microscopy and sowing on Sabur agar at a temperature of 27° C for up to 2 weeks.
Keywords: тези доповідей